2017
DOI: 10.1002/pola.28637
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene and poly(ethylene-co -1-octene) effective synthesis with diamine-bis(phenolate) complexes: Effect of complex structure on catalyst activity and product microstructure

Abstract: A series of group 4 metal complexes bearing amine-bis(phenolate) ligands with the amino side-arm donor: (l-O)2 (2d) are used in ethylene and propylene homopolymerization, and ethylene/1-octene copolymerization. All complexes, upon their activation with Al(iBu) 3 /Ph 3 CB(C 6 F 5 ) 4 , exhibit reasonable catalytic activity for ethylene homo-and copolymerization giving linear polyethylene with high to ultra-high molecular weight (600Á3 10 3 -3600Á3 10 3 g/mol). The activity of 1a/Al(iBu) 3 /Ph 3 CB(C 6 F 5 ) 4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…The microstructure of E-NB copolymers depends on the catalyst applied with the highest diads contents for the (L3) 2 VCl 2 and higher microblocks for the (L2) 2 VCl 2 complexes. Comparison to the Fujita catalyst studied in very similar reaction conditions (pressure, hexane solvent, AlEt 2 Cl cocatalyst, temperature) [43,44] shows that the presented 2-hydroxyphenyloxazoline catalysts reveal slightly better performance for titanium but are considerably higher for the vanadium atom center. This opens the way for further studies and changes in the structure of ligands that allow us to obtain complexes capable of producing stereoregular polymers with good yield.…”
Section: Discussionmentioning
confidence: 95%
“…The microstructure of E-NB copolymers depends on the catalyst applied with the highest diads contents for the (L3) 2 VCl 2 and higher microblocks for the (L2) 2 VCl 2 complexes. Comparison to the Fujita catalyst studied in very similar reaction conditions (pressure, hexane solvent, AlEt 2 Cl cocatalyst, temperature) [43,44] shows that the presented 2-hydroxyphenyloxazoline catalysts reveal slightly better performance for titanium but are considerably higher for the vanadium atom center. This opens the way for further studies and changes in the structure of ligands that allow us to obtain complexes capable of producing stereoregular polymers with good yield.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the activating effect of the comonomer on the copolymerization yield was observed independently on the comonomer concentration. Its activity was over four times higher in ethylene/1-octene copolymerization than in ethylene homopolymerization [30]. In contrast, the titanium complexes Ti-1-Ti-4 bearing the same type of tetradentate ligand in conjunction with Al(iBu) 3 /Ph 3 CB(C 6 F 5 ) 4 exhibited the negative comonomer effect and lower activity than the zirconium catalyst.…”
Section: Complexes Of Group 4 Transition Metalsmentioning
confidence: 95%
“…Interestingly, Ti-4 produced the ethylene/1-octene copolymer, not only with a high incorporation level, but at the same time with the very high molecular weight and very narrow molecular weight distribution (M w = 755,000 g/mol, M w /M n = 1.7). The introduction of sterically bulkier N(iPr) 2 pendant donor group in the complexes Ti-2 and Ti-3 resulted in lower 1-octene contents: 5.1 mol% and 2.8 mol%, respectively [30]. Further studies [31] showed that the presence of AlMe 3 in the feed during the copolymerization catalyzed by Zr-6/Al(iBu) 3 /Ph 3 CB(C 6 F 5 ) 4 lowered the catalyst activity and greatly increased the amount of comonomer content in the copolymer from about 10 to approximately 40 mol% for 1-octene and 31 mol% for 1-hexene when the AlMe 3 /Zr molar ratio was equal to 100/1.…”
Section: Complexes Of Group 4 Transition Metalsmentioning
confidence: 99%
“…26−35 In contrast, the symmetric amine bis(phenolate) group 4 transition metal complexes IIA 10,25 show relatively high catalytic activities for 1-olefine polymerization reactions, but produce atactic polymers. The nonsymmetric amine bis(phenolate) group 4 transition metal complexes IIB 36,37 and the bis[amine bis(phenolate)]zirconium complexes IIC 38,39 were reported to show low to moderate tacticity-control. So far, most of the mononuclear IIA and IIB type of titanium and zirconium complexes were reported to exhibit very low catalytic activities for ethylene polymerization.…”
Section: ■ Introductionmentioning
confidence: 99%